Blanching-induced modulation of polyphenol oxidase, antioxidants, and phenolic profiles in mangosteen pericarp - Mohamad Azman, Ezzat; Anwar, Farooq; Mohd Adzahan, Noranizan; Sulaiman, Rabiha; Mohamed Nawawi, Nur Izzati; Ijod, Giroon (Faculty of Food Technology and Biotechnology, University of Zagreb, Croatia, 2024)
Research background. Anthocyanin pigments in mangosteen pericarp (MP) can serve as natural colourants; however, their stability is compromised by enzymatic browning caused by polyphenol oxidase (PPO). Thus, this study aimed to investigate how hot water and steam blanching affect the PPO activity, phenolic profile, and antioxidant properties of MP. Experimental approach. Fresh MP was blanched for 0, 30, 60, 90, and 120 s at 100 °C in hot water and steam, and the residual PPO activity, total phenolic content (TPC), total anthocyanins, antioxidant activities, browning index, and colour characteristics were evaluated. Additionally, phenolic compounds were identified using liquid chromatography-mass spectrometry (LC-MS). Results and conclusions. Following zero-order reaction kinetics (R2>0.800), a significant reduction (p<0.05) in residual PPO activity was observed in both blanched MP. As expected, PPO was inactivated more rapidly in hot water (t1/2=~59.1 s) than in steam blanching (t1/2=~121.1 s). However, the principal component analysis (PCA) revealed that steam blanching for 90 s was the most efficient method, preserving the highest levels of antioxidant capacity (~9135.60 µmol TE/g), ferric-reducing power (~9729.00 µmol TE/g), total anthocyanins (~3.03 mg/g), and TPC (~1056.66 mg GAE/g). Overall, 90 s of steam blanching was the most efficient method because of its ability to preserve phenolic compounds, and it is also a cost-effective method compared to hot water, which needs to be replaced after a few uses. Novelty and scientific contribution. This is the first study to report the effects of blanching on anthocyanins predominantly present in MP, specifically cyanidin-3-O-sophoroside (C3S) and cyanidin-3-O-glucoside (C3G), using high-performance liquid chromatography (HPLC) and liquid chromatography-mass spectrometry (LC-MS). This study makes a significant scientific contribution to the food industry by providing suitable blanching techniques to maintain the quality of bioactive compounds, specifically anthocyanins in MP, which can be used as a natural colourant.